Bioethical aspects of the use of biometric identifiers - Lucero M., Boris A.; Saracini, Chiara; Mora, Marco; Muñoz Quezada, María Teresa (Acta Bioethica, 2020)
Biometrics has had a rapid expansion as a technology, being increasingly accessible to the public, and lending utility to governments and society in the management of citizen security. It is applied either for verification or for identification of an individual’s identity and technically constitutes a problem of pattern recognition. In Chile, the existing legal framework regarding the handling of personal data does not include specific biometrics in its regulation. A new bill that considers both biometric data and Biological profiles is in process. In addition, we revised the international reports of the last two decades that analyze the use of biometrics. The primary focus of concern of these documents, from the ethical point of view, is the right to privacy of individuals, giving practical guidance and discussion regarding the elements necessary for the application of these novel technologies in an appropriate ethically manner. Finally, we contextualize from a brief analysis of biopolitics the role of biometrics and the basic ethical requirements for its development in that framework.